Beyond Chemistry: Investigating the Physical, Pharmacological, and Computational Aspects of Polyoxometalate Integrated Solid Lipid Nanoparticles for Cancer Treatment - Khan R; Tulain UR; Shah HS; Usman F; Chohan TA; Iqbal J; Kazi M; Ijaz M; Erum A; Malik NS; Mahmood A (International Journal of Nanomedicine)
Riffat Khan,1 Ume Ruqia Tulain,1 Hamid Saeed Shah,2 Faisal Usman,3 Tahir Ali Chohan,2 Jamshed Iqbal,4 Mohsin Kazi,5 Muhammad Ijaz,6 Alia Erum,1 Nadia Shamshad Malik,7 Arshad Mahmood8,9 1Faculty of Pharmacy, University of Sargodha, Sargodha, 40100, Pakistan; 2Institute of Pharmaceutical Sciences, University of Veterinary and Animal Sciences, Lahore, 54000, Pakistan; 3Department of Pharmaceutics, Faculty of Pharmacy, Bahauddin Zakariya University, Multan, 66000, Pakistan; 4Centre for Advanced Drug Research, COMSATS University Islamabad, Abbottabad Campus, Abbottabad, 22060, Pakistan; 5Department of Pharmaceutics, College of Pharmacy, King Saud University, Riyadh, 11451, Saudi Arabia; 6Department of Pharmacy, COMSATS University Islamabad, Lahore Campus, Lahore, Pakistan; 7Faculty of Pharmacy, Capital University of Science and Technology, Islamabad, Pakistan; 8College of Pharmacy, Al-Ain University, Abu Dhabi Campus, Abudhabi, United Arab Emirates; 9AAU Health and Biomedical Research Center, Al Ain University, Abu Dhabi, United Arab EmiratesCorrespondence: Ume Ruqia Tulain; Muhammad Ijaz, Email umeruqia.tulain@uos.edu.pk; drmijaz@cuilahore.edu.pkPurpose: The solid lipid nanoparticles of transitional metal complexes (POMs) were prepared with natural lipids with the aim of developing a safer therapeutic approach for cancer treatment.Methods: Natural lipids were used to create solid lipid nanoparticles containing transitional metal complexes (POMs).Results: The nanoparticles had displayed appreciable entrapment and loading percentage of P5W30. The zeta capacitance was measured to be − 32.57± 6.44 mV with average particle dimension of 160.5± 8.61 nm and polydispersity index (PDI) of around 0.3814± 0.096. The effectiveness of P5W30-BW-SLNs in inhibiting the growth of HeLa cells was found to be higher (IC50 = 3.02± 2.14 μg/mL) compared to pure P5W30 (IC50 = 7.93± 5.08 μg/mL). Further examinations of DNA damage were made through comet test and flow cytometry techniques. The assessment of tumor regression and survival was conducted, and comparison was recorded. The P5W30-BW-SLNs resulted in a 72.91% increase in survival rates and a reduction in tumor burden by 2.967± 0.543%. Moreover, the computational findings demonstrate a strong connection with the actual data, providing a plausible explanation for the notable chemopreventive efficacy of POM against HeLa cell lines.Conclusion: The study’s findings might pave the way for a more efficient delivery system in cancer treatment. Keywords: polyoxometalate, beeswax, nanoparticle, molecular docking